Acquiring firm characteristics and stock market efficiency: a case study approach. (3rd August 2005) - Lin, Lin; Piesse, Jenifer; Chou, De-Wai
Previous studies have considered the market for corporate control, but have tended to assume that this is a strategy undertaken by financially robust acquiring firms. This paper provides five case studies that reflect that both acquirers and targets have differing financial characteristics. In depth examination has found that the ambiguous results in the literature are due to a lack of understanding of the complexity and diversity of takeover participants. These results indicate that while the market is efficient, there are a number of different effects of takeover that relate to the diverse nature of firms and their environment.